La coordinación óculo-manual en el remate del voleibol - García Japón, Alexander Vinicio (2024)
The research named as “Eye-Hand Coordination in Volleyball Spikes” emphasizes the significance of enhancing eye-hand coordination skill, both within the realm of sports performance and in fostering motor and cognitive development among youth. Its primary aim is to equip teachers and coaches with effective training tools and guidelines personalised to improving volleyball spike techniques. To achieve this goal, this research includes a diagnostic test and observation sheet designed to assess eye-hand coordination; specifically in high school students during volleyball spikes. Through careful observation, the study identified common challenges that students encounter when executing the spike. Hence, it enables the proposal of targeted solutions that contribute to the enhancement of motor and technical abilities in young athletes. The practical implications of these findings are substantial, offering actionable insights for coaches and Physical Education instructors to refine their training programs and enhance players’ hand-eye coordination in the context of volleyball.